Neuronal coding of multiscale temporal features in communication sequences within the bat auditory cortex. (December 2018) - García-Rosales, Francisco; Beetz, M.; Cabral-Calderin, Yuranny; Kössl, Manfred; Hechavarria, Julio
Abstract Experimental evidence supports that cortical oscillations represent multiscale temporal modulations existent in natural stimuli, yet little is known about the processing of these multiple timescales at a neuronal level. Here, using extracellular recordings from the auditory cortex (AC) of awake bats (Carollia perspicillata ), we show the existence of three neuronal types which represent different levels of the temporal structure of conspecific vocalizations, and therefore constitute direct evidence of multiscale temporal processing of naturalistic stimuli by neurons in the AC. These neuronal subpopulations synchronize differently to local-field potentials, particularly in theta- and high frequency bands, and are informative to a different degree in terms of their spike rate. Interestingly, we also observed that both low and high frequency cortical oscillations can be highly informative about the listened calls. Our results suggest that multiscale neuronal processing allows for the precise and non-redundant representation of natural vocalizations in the AC. García-Rosales et al. identified three distinct neuronal populations within the auditory cortex of awakeCarollia perspicillata bats. These neurons responded to different temporal features of communication calls from conspecifics and synchronized to distinct cortical oscillations, suggesting multiscale temporal representation at a cellular level.